Preparation method of biodegradable PBST-PLA copolymer and biodegradable PBST-PLA copolymer

In the preparation of PBST-PLA copolymer, the esterification reaction and polycondensation reaction were carried out separately, and PLA was added after cooling, which solved the problems of low tensile strength and elongation of break of existing copolymers, and achieved high strength and low strength Cost copolymer preparation.

CN119431805APending Publication Date: 2025-02-14CHINESE TEXTILE ACAD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310971589.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing PBST-PLA copolymer has low tensile strength and elongation at break, and the need for secondary drying leads to high production costs, which cannot meet the application requirements of high strength and low cost.

Method used

By esterifying succinic acid and terephthalic acid with butanediol, the intermediate product is obtained and pre-polycondensation and final polycondensation reaction is carried out. Then, after cooling, PLA is added for reaction, and finally, it is prepared by extrusion and granulation. Biodegradable PBST-PLA copolymer.

Benefits of technology

The tensile strength, modulus and elongation of break of the PBST-PLA copolymer are improved, the secondary drying step is avoided, the production cost is reduced, and the high molecular weight and good mechanical properties of the copolymer are ensured.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a biodegradable PBST-PLA copolymer and the biodegradable PBST-PLA copolymer, the preparation method comprises the following steps: (1) mixing succinic acid, butanediol and a first catalyst for esterification reaction to obtain a first intermediate product; (2) mixing terephthalic acid, butanediol and a second catalyst for esterification reaction to obtain a second intermediate product; (3) mixing the first intermediate product, the second intermediate product and a polycondensation catalyst, and carrying out a pre-polycondensation reaction to obtain a pre-polycondensation product; and (4) carrying out final polycondensation reaction on the pre-polycondensation product, cooling after polymerization reaches a certain molecular weight, adding PLA, reacting, discharging, extruding and granulating to obtain the biodegradable PBST-PLA copolymer. The PBST-PLA copolymer obtained by the preparation method disclosed by the invention has the advantages of good film blowing property, high strength, good toughness and complete biodegradability, and the preparation process is relatively simple and suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable polymer preparation, and in particular relates to a preparation method of a biodegradable PBST-PLA copolymer and the biodegradable PBST-PLA copolymer. Background Art

[0002] Polybutylene terephthalate-co-succinate (PBST) is a kind of aliphatic-aromatic copolyester. Under the appropriate composition range, PBST is biodegradable and has mechanical properties superior to aliphatic polyesters. PBST polymer products can be used for blown film and have the characteristics of being biodegradable, thus realizing the cycle in nature. Therefore, they are widely used in the fields of agricultural mulch, supermarket shopping bags, etc., and are ideal green polymer materials. However, in existing applications, PBST polymer products have low strength and modulus, and are soft in texture, which limits their further application in a wider range of fields.

[0003] Polylactic acid (PLA) is another important biodegradable resin and one of the most widely used polymers in the field of biodegradation. However, PLA has disadvantages such as low melt strength, poor toughness, lack of flexibility and elasticity, and poor heat resistance, which limits its application. Blending PBST with PLA to obtain biodegradable products can take advantage of the complementary properties of the two and broaden the application scenarios of the resulting polymer products.

[0004] In the prior art, PBST-PLA copolymers are usually prepared by blending PBST and PLA using a twin-screw extruder, such as the patent application with publication number CN114015210A. However, the tensile strength and elongation at break of the copolymer material obtained by the twin-screw extrusion blending are both low, and the production cost is high, especially in the field of film production, and it cannot meet the application requirements of high-strength, high-elongation film and low-cost occasions. At the same time, the copolymer material obtained by the above method needs secondary drying before it can be used to make copolymer products, which affects its wide application.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a biodegradable PBST-PLA copolymer and a biodegradable PBST-PLA copolymer, which can solve the problems that the tensile strength and elongation at break of the copolymer material obtained in the existing blending preparation method are low, and the cost is high due to the need for secondary drying.

[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0008] A method for preparing a biodegradable PBST-PLA copolymer comprises the following steps:

[0009] (1) mixing succinic acid, butanediol and a first catalyst to carry out an esterification reaction to obtain a first intermediate product;

[0010] (2) mixing terephthalic acid, butanediol and a second catalyst to carry out an esterification reaction to obtain a second intermediate product;

[0011] (3) mixing the first intermediate product, the second intermediate product and a polycondensation catalyst to perform a pre-polycondensation reaction to obtain a pre-polycondensation product;

[0012] (4) The pre-polycondensation product is subjected to a final polycondensation reaction. After the polymerization reaches a certain molecular weight, the temperature is lowered, PLA is added to react, and then extruded and granulated to obtain a biodegradable PBST-PLA copolymer.

[0013] In the present invention, terephthalic acid and succinic acid are esterified with butanediol respectively, which can reduce the generation of by-products. The two intermediate products (i.e., esterification products) obtained are mixed again for polymerization, and a PBST polymer with a certain molecular weight is obtained after polycondensation reaction and final polycondensation reaction, and then PLA is added to react after cooling, and finally extrusion granulation is performed to prepare a biodegradable PBST-PLA copolymer. Through the above preparation method, PLA segments are introduced into the PBST main chain to form a copolymer, which can increase tensile strength, modulus, and elongation at break compared with pure PBST. More importantly, the PBST-PLA copolymer obtained by the above scheme has a long copolymerization reaction time of PLA and PBST, and the reaction is sufficient, which avoids the problems of short reaction time (usually only 2 to 3 minutes) of twin-screw extrusion blending in the prior art, secondary drying of raw materials, and reduced molecular weight of copolymer.

[0014] On the other hand, if PLA is added before the polymerization of the first intermediate product and the second intermediate product, or during the polymerization, it will usually affect the polymerization process and it will be difficult to prepare a copolymer with a high molecular weight. At the same time, the stirring and dispersion effect of PLA in the esterification product melt is not ideal, and the effect of improving the mechanical properties of the copolymer material is not obvious.

[0015] Furthermore, in step (4), the temperature is lowered to 190-210° C., PLA is added for reaction, the reaction temperature is maintained at 190-210° C., and the reaction time is 20-50 min;

[0016] Preferably, the reaction temperature is 200-210°C and the reaction time is 30-40 min;

[0017] Preferably, after the reaction is completed, nitrogen is introduced to pressurize the material for discharging;

[0018] Preferably, nitrogen is introduced and pressurized to 3-4 Kgf / cm 2 Carry out discharging.

[0019] In the above scheme, the reaction temperature and reaction time are controlled within the above range, which is conducive to improving the conversion rate of the reaction, so that PLA and PBST can fully copolymerize, ensuring that the copolymer has a high molecular weight, and at the same time ensuring that the introduction of PLA effectively improves the mechanical properties of the resulting copolymer. In addition, it is also conducive to controlling the degree of polymerization of the copolymer product within a suitable range, and obtaining a PBST-PLA copolymer material that has both biodegradable properties and is suitable for film products made by film blowing process.

[0020] Furthermore, in step (4), the reaction temperature of the final polycondensation reaction is 250 to 260° C., preferably 255 to 260° C.;

[0021] Preferably, when the intrinsic viscosity of the melt is 1.25 to 1.30 dL / g, the temperature is lowered;

[0022] More preferably, the final polycondensation reaction is carried out in a polymerization kettle, and when the intrinsic viscosity of the melt is 1.25-1.30 dL / g, the melt is transported to a blending kettle for cooling, and PLA is added.

[0023] In the above scheme, the product of the final polycondensation reaction is transported to a blending kettle, and then PLA and PBST melt are added to the blending kettle for mixed copolymerization. Compared with the method of directly adding PLA to the polymerization kettle, the blending kettle can more fully stir the reaction materials inside, so that PLA is fully and evenly dispersed in the PBST melt, further enhancing the effect of copolymerization of PLA and PBST on improving the performance of the resulting copolymer.

[0024] For polymer compounds, there is a correlation between their molecular weight and intrinsic viscosity. In the present invention, the intrinsic viscosity of the melt in the polymerization kettle is detected online. When the measured intrinsic viscosity falls within a specific range, it can be transported to the blending kettle and added with PLA after waiting for cooling. In this way, the end timing of the final polycondensation reaction can be accurately controlled to ensure the subsequent copolymerization effect with PLA.

[0025] Furthermore, during the final polycondensation reaction, the vacuum degree in the polymerization kettle is controlled to be 60 to 150 Pa, preferably 60 to 100 Pa;

[0026] Preferably, the polymerization kettle is evacuated for a period of 40 to 70 minutes, preferably 50 to 60 minutes.

[0027] Specifically, in the present invention, the pre-polycondensation reaction is also carried out in the above-mentioned polymerization kettle, and the melt in the polymerization kettle is stirred in both the pre-polycondensation reaction and the final polycondensation reaction stages. After the pre-polycondensation reaction stage is completed, the polymerization kettle is slowly evacuated, and the temperature is increased to carry out the final polycondensation reaction. After the PBST melt with a certain molecular weight is obtained by the final polycondensation reaction, the stirring is stopped, the vacuum is turned off, nitrogen is introduced for pressurization, the melt is pumped into the blending kettle, the temperature is lowered, a certain amount of PLA is added, and after a period of reaction, the blending kettle is filled with nitrogen for pressurization to discharge the material, and the PBST-PLA copolymer is prepared by extrusion, cooling, and pelletizing.

[0028] Furthermore, in step (4), PLA is in powder form, the mesh size of the PLA powder is 100-150 mesh, preferably 130-150 mesh, and the addition amount is 10%-25% of the mass of the melt, preferably 15%-20%.

[0029] In the above scheme, PLA in powder form is more easily and evenly dispersed in the PBST melt, thereby further ensuring that the copolymerization reaction of PBST and PLA is fully carried out.

[0030] Furthermore, in step (4), a functional additive is added after cooling, and the amount of the functional additive added is 0.05% to 0.10% of the mass of the melt;

[0031] More preferably, the functional auxiliary agent is pyromellitic anhydride, and its purity is preferably 98.0% to 99.9%.

[0032] Furthermore, in step (1), the molar ratio of succinic acid to butanediol is 1:1.20-1.30, preferably 1:1.25-1.30; in step (2), the molar ratio of terephthalic acid to butanediol is 1:2-4, preferably 1:2-3;

[0033] Preferably, the first catalyst is tetrabutyl titanate, and the second catalyst is tetraisopropyl titanate;

[0034] More preferably, the molar amount of the first catalyst is 0.01% to 0.03% of the molar amount of the succinic acid, preferably 0.02% to 0.03%; the molar amount of the second catalyst is 0.01% to 0.03% of the molar amount of the terephthalic acid, preferably 0.02% to 0.03%.

[0035] Furthermore, in step (1), the reaction temperature of the esterification reaction is 165-175° C., preferably 165-170° C.; the esterification rate reaches 98%-99.5%, and the first intermediate product is obtained;

[0036] In step (2), the reaction temperature of the esterification reaction is 245-255° C., preferably 250-255° C.; the esterification rate reaches 98%-99.5%, and the second intermediate product is obtained.

[0037] Specifically, in step (1) of the preparation method of the present invention, the succinic acid, butanediol and the first catalyst are added to a first esterification kettle to carry out an esterification reaction. In step (2), the terephthalic acid, butanediol and the second catalyst are added to a second esterification kettle to carry out an esterification reaction.

[0038] Controlling the raw material ratio and reaction temperature within the above range is conducive to improving the conversion rate of the two esterification reactions, thereby reducing the impact of by-products on subsequent reactions and avoiding the impact of by-products in the esterification reaction stage on the quality of the final copolymer product.

[0039] Furthermore, in step (3), the mass ratio of the first intermediate product to the second intermediate product is 1:0.8-1.2, preferably 1:0.8-1.0;

[0040] Preferably, the amount of the polycondensation catalyst is 0.02% to 0.04%, preferably 0.02% to 0.03%, of the total mass of succinic acid in step (1) and terephthalic acid in step (2);

[0041] More preferably, the polycondensation catalyst is tetraisopropyl titanate.

[0042] In the above scheme, the mass ratio of the first intermediate product to the second intermediate product is controlled within the above range, which can maintain a balance between the strength and biodegradability of the obtained copolymer material.

[0043] Specifically, in the present invention, the first intermediate product is pumped into the polymerization kettle through a first melt metering pump, and the second intermediate product is pumped into the polymerization kettle through a second melt metering pump, and mixed evenly to obtain an esterified melt mixture, and then the measured condensation catalyst is added from the feeding port of the polymerization kettle, and stirring and mixing are started to carry out a pre-condensation reaction.

[0044] Furthermore, in step (3), the reaction temperature of the pre-polycondensation reaction is 230-245° C., and the reaction time is 30-50 min;

[0045] Preferably, the reaction temperature of the pre-polycondensation reaction is 240-245° C., and the reaction time is 35-45 min.

[0046] In the above scheme, by controlling the reaction temperature and reaction time of the pre-polycondensation reaction stage, the conversion rate of the pre-polycondensation reaction stage can be improved, which is beneficial to obtain a polymer with a higher molecular weight in the subsequent final polycondensation reaction stage.

[0047] In step (4), the melt that reaches a certain molecular weight through final polycondensation reaction enters the blending kettle at a feed rate of 200 to 300 kg / h.

[0048] In the present invention, controlling the feed flow rate of the blending kettle within the above range is beneficial to controlling the temperature of the copolymerization reaction in the blending kettle, and making the copolymerization reaction have a longer reaction time, ensuring the full progress of the copolymerization reaction and ensuring the high molecular weight of the copolymerization product.

[0049] The present invention also provides a biodegradable PBST-PLA copolymer, wherein the biodegradable PBST-PLA copolymer has a tensile strength of 35 to 40 MPa and an elongation at break of 600 to 900%.

[0050] Preferably, the biodegradable PBST-PLA copolymer is prepared by the above-mentioned method for preparing the biodegradable PBST-PLA copolymer.

[0051] The biodegradable PBST-PLA copolymer described above has high tensile strength and elongation at break, which is beneficial to expanding the application scope of biodegradable materials, and is particularly suitable for making biodegradable film products by film blowing process.

[0052] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.

[0053] 1. The preparation method of the present invention obtains a melt of PBST by polymerization reaction, and then directly adds PLA into the melt for mixing and copolymerization, thereby obtaining a PBST-PLA copolymer, which eliminates the trouble of secondary drying of pure resin raw materials in the prior art, saves production costs, and has a long copolymerization time, a more complete reaction, ensures that the copolymer has a high molecular weight, and the obtained copolymer product has higher tensile strength and elongation at break.

[0054] 2. When PBST is prepared by polymerization reaction, succinic acid and terephthalic acid are separated and esterified with butanediol respectively to obtain two intermediate products, which are then mixed and polymerized. This can reduce the production of by-products in the esterification reaction stage and further ensure the mechanical properties of the resulting copolymer.

[0055] 3. The PBST-PLA copolymer obtained by the present invention has good film blowing properties, high strength, good toughness, is completely biodegradable, and has a relatively simple preparation process, and is suitable for industrial-scale production.

[0056] The specific embodiments of the present invention are described in further detail below. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0058] Example 1

[0059] This example is carried out according to the following steps to prepare the biodegradable PBST-PLA copolymer:

[0060] (1) adding succinic acid, butanediol and tetrabutyl titanate catalyst to a first esterification kettle and mixing them, wherein the amount of succinic acid added is 100 kg, the molar ratio of succinic acid to butanediol is 1:1.20, and the molar amount of tetrabutyl titanate is 0.02% of the molar amount of succinic acid; controlling the reaction temperature to be 165° C. to carry out an esterification reaction, and the esterification rate reaches 99.0%, thereby obtaining a first intermediate product;

[0061] (2) adding terephthalic acid, butanediol and tetraisopropyl titanate catalyst to a second esterification kettle and mixing them, wherein the amount of terephthalic acid added is 100 kg, the molar ratio of terephthalic acid to butanediol is 1:2, and the molar amount of tetraisopropyl titanate is 0.02% of the molar amount of terephthalic acid; controlling the reaction temperature to 250° C. to carry out esterification reaction, the esterification rate reaches 99.0%, and a second intermediate product is obtained;

[0062] (3) The first intermediate product and the second intermediate product were respectively pumped into the polymerization kettle at a mass ratio of 1:1, mixed evenly, and a polycondensation catalyst tetraisopropyl titanate was added in an amount of 0.02% of the total mass of succinic acid and terephthalic acid, stirred and mixed, and a pre-polycondensation reaction was carried out. The reaction temperature was controlled at 245° C. and the reaction time was 50 min to obtain a pre-polycondensation product;

[0063] (4) slowly evacuating the polymerization kettle for 70 minutes, controlling the vacuum degree at 60 Pa, slowly raising the temperature to allow the pre-polycondensation product to undergo a final polycondensation reaction, and controlling the reaction temperature at 260° C.; when the intrinsic viscosity is 1.25 dL / g, stopping stirring, turning off the vacuum, introducing nitrogen to increase the pressure, and pumping the melt into the blending kettle;

[0064] Cool down, control the reaction temperature inside the blending kettle to 200°C, add PLA powder and pyromellitic anhydride, the mesh size of PLA powder is 100 mesh, the addition amount is 10% of the melt mass, the purity of pyromellitic anhydride is 99.9%, the addition amount is 0.05% of the melt mass; after reacting for 30 minutes, fill with nitrogen at 3-4 kgf / cm 2 The material is discharged under pressure, extruded, cooled, and pelletized to obtain a biodegradable PBST-PLA copolymer.

[0065] Example 2

[0066] This example is carried out according to the following steps to prepare the biodegradable PBST-PLA copolymer:

[0067] (1) adding succinic acid, butanediol and tetrabutyl titanate catalyst to a first esterification kettle and mixing them, wherein the amount of succinic acid added is 100 kg, the molar ratio of succinic acid to butanediol is 1:1.20, and the molar amount of tetrabutyl titanate is 0.02% of the molar amount of succinic acid; controlling the reaction temperature to be 165° C. to carry out an esterification reaction, and the esterification rate reaches 99.0%, thereby obtaining a first intermediate product;

[0068] (2) adding terephthalic acid, butanediol and tetraisopropyl titanate catalyst to a second esterification kettle and mixing them, wherein the amount of terephthalic acid added is 100 kg, the molar ratio of terephthalic acid to butanediol is 1:2, and the molar amount of tetraisopropyl titanate is 0.02% of the molar amount of terephthalic acid; controlling the reaction temperature to 250° C. to carry out esterification reaction, the esterification rate reaches 99.0%, and a second intermediate product is obtained;

[0069] (3) The first intermediate product and the second intermediate product were respectively pumped into the polymerization kettle at a mass ratio of 1:1, mixed evenly, and a polycondensation catalyst tetraisopropyl titanate was added in an amount of 0.02% of the total mass of succinic acid and terephthalic acid, stirred and mixed, and a pre-polycondensation reaction was carried out. The reaction temperature was controlled at 245° C. and the reaction time was 50 min to obtain a pre-polycondensation product;

[0070] (4) slowly evacuating the polymerization kettle for 70 minutes, controlling the vacuum degree at 60 Pa, slowly raising the temperature to allow the pre-polycondensation product to undergo a final polycondensation reaction, and controlling the reaction temperature at 260° C.; when the intrinsic viscosity is 1.30 dL / g, stopping stirring, turning off the vacuum, introducing nitrogen to increase the pressure, and pumping the melt into the blending kettle;

[0071] Cool down, control the reaction temperature inside the blending kettle to 210°C, add PLA powder and pyromellitic anhydride, the mesh number of PLA powder is 150 mesh, the addition amount is 20% of the melt mass, the purity of pyromellitic anhydride is 99.9%, the addition amount is 0.05% of the melt mass; after reacting for 30 minutes, fill with nitrogen at 3-4 kgf / cm 2 The material is discharged under pressure, extruded, cooled, and pelletized to obtain a biodegradable PBST-PLA copolymer.

[0072] Comparative Example 1

[0073] This comparative example was carried out according to the following method to prepare the PBST-PLA copolymer:

[0074] 100 kg of dried PBST resin (with an intrinsic viscosity of 1.25 dL / g), 10 kg of PLA powder (with a mesh size of 100 mesh), and 50 g of pyromellitic anhydride (with a purity of 99.9%) were stirred at high speed.

[0075] Then the reaction extrusion was carried out in a twin-screw extruder, wherein the screw speed was 100 rpm and the relative vacuum degree was -0.6 Kgf / cm 2 The temperature of each zone of the twin-screw extruder is: the temperature of zone 1 is 185-190°C, the temperature of zone 2 is 190-200°C, the temperature of zone 3 is 200-210°C, and the temperature of the die head is 200-210°C;

[0076] After extrusion, the mixture is cooled and pelletized to obtain PBST-PLA copolymer.

[0077] Comparative Example 2

[0078] This comparative example was carried out according to the following method to prepare the PBST-PLA copolymer:

[0079] 100 kg of dried PBST resin (with an intrinsic viscosity of 1.30 dL / g), 20 kg of PLA powder (with a mesh size of 150 mesh), and 50 g of pyromellitic anhydride (with a purity of 99.9%) were stirred at high speed.

[0080] Then the reaction extrusion was carried out in a twin-screw extruder, wherein the screw speed was 100 rpm and the relative vacuum degree was -0.6 Kgf / cm 2 The temperature of each zone of the twin-screw extruder is: the temperature of zone 1 is 185-190°C, the temperature of zone 2 is 190-200°C, the temperature of zone 3 is 200-210°C, and the temperature of the die head is 200-210°C;

[0081] After extrusion, the mixture is cooled and pelletized to obtain PBST-PLA copolymer.

[0082] Comparative Example 3

[0083] This comparative example was carried out according to the following steps to prepare the PBST-PLA copolymer:

[0084] (1) adding succinic acid, terephthalic acid, butanediol and tetrabutyl titanate catalyst into an esterification kettle and mixing them, wherein the amount of succinic acid added is 200 kg, the amount of terephthalic acid added is 180 kg, the amount of butanediol added is 350 kg, and the amount of tetrabutyl titanate catalyst added is 30 g; controlling the reaction temperature to 210° C. to carry out esterification reaction, the esterification rate reaches 99.0%, and obtaining an esterified melt;

[0085] (2) pumping the esterified product melt into a polymerization kettle, adding a polycondensation catalyst tetraisopropyl titanate in an amount of 76 g, stirring and mixing, and performing a pre-polycondensation reaction. The reaction temperature is controlled at 245° C. and the reaction time is 50 min to obtain a pre-polycondensation product;

[0086] (3) slowly evacuating the polymerization kettle for 70 minutes, controlling the vacuum degree at 60 Pa, slowly raising the temperature to allow the pre-polycondensation product to undergo a final polycondensation reaction, and controlling the reaction temperature at 260° C.; when the intrinsic viscosity is 1.25 dL / g, stopping stirring, turning off the vacuum, introducing nitrogen to increase the pressure, and pumping the melt into the blending kettle;

[0087] Cool down, control the reaction temperature inside the blending kettle to 200°C, add PLA powder and pyromellitic anhydride, the mesh size of PLA powder is 100 mesh, the addition amount is 10% of the melt mass, the purity of pyromellitic anhydride is 99.9%, the addition amount is 0.05% of the melt mass; after reacting for 30 minutes, fill with nitrogen at 3-4 kgf / cm 2 The material is discharged under pressure, extruded, cooled, and pelletized to obtain a biodegradable PBST-PLA copolymer.

[0088] Comparative Example 4

[0089] This comparative example was carried out according to the following steps to prepare the PBST-PLA copolymer:

[0090] (1) adding succinic acid, butanediol and tetrabutyl titanate catalyst to a first esterification kettle and mixing them, wherein the amount of succinic acid added is 100 kg, the molar ratio of succinic acid to butanediol is 1:1.20, and the molar amount of tetrabutyl titanate is 0.02% of the molar amount of succinic acid; controlling the reaction temperature to be 165° C. to carry out an esterification reaction, and the esterification rate reaches 99.0%, thereby obtaining a first intermediate product;

[0091] (2) adding terephthalic acid, butanediol and tetraisopropyl titanate catalyst to a second esterification kettle and mixing them, wherein the amount of terephthalic acid added is 100 kg, the molar ratio of terephthalic acid to butanediol is 1:2, and the molar amount of tetraisopropyl titanate is 0.02% of the molar amount of terephthalic acid; controlling the reaction temperature to 250° C. to carry out esterification reaction, the esterification rate reaches 99.0%, and a second intermediate product is obtained;

[0092] (3) The first intermediate product and the second intermediate product are pumped into the polymerization kettle at a mass ratio of 1:1, mixed evenly, and a polycondensation catalyst tetraisopropyl titanate is added, the addition amount of which is 0.02% of the weight of succinic acid and terephthalic acid, and PLA powder and pyromellitic anhydride are also added, the mesh size of the PLA powder is 100 mesh, the addition amount is 10% of the melt mass, and the purity of pyromellitic anhydride is 99.9%, and the addition amount is 0.05% of the melt mass; stirring and mixing, performing a pre-polycondensation reaction, the reaction temperature is controlled at 245°C, the reaction time is 50min, and a pre-polycondensation product is obtained;

[0093] (4) The polymerization kettle was slowly evacuated for 70 minutes, the vacuum degree was controlled at 60 Pa, and the temperature was slowly increased to allow the pre-polycondensation product to undergo a final polycondensation reaction, and the reaction temperature was controlled at 260° C. When the intrinsic viscosity reached 1.25 dL / g, stirring was stopped, the vacuum was turned off, nitrogen was introduced to pressurize the material for discharge, and then extruded, cooled, and pelletized to obtain a PBST-PLA copolymer.

[0094] Test Example 1

[0095] In this test example, the mechanical properties of the PBST-PLA copolymers prepared in the above examples and comparative examples were tested in the following manner.

[0096] Tensile strength: The tensile strength of the copolymer product was tested using the ASTM D638 standard method. The greater the tensile strength, the stronger the rigidity of the molecular chain of the product.

[0097] Elongation at break: The elongation at break of the copolymer product was tested using the ASTM D638 standard method. The greater the elongation at break, the better the toughness of the product.

[0098] The test results of this test example are shown in Table 1 below.

[0099] Table 1 Mechanical properties test results

[0100] Tensile strength / MPa Elongation at break / % Example 1 35 850 Example 2 43 740 Comparative Example 1 26 390 Comparative Example 2 29 300 Comparative Example 3 25 400 Comparative Example 4 27 480

[0101] By comparing Example 1 with Comparative Example 1, and Example 2 with Comparative Example 2, it can be seen that the biodegradable PBST-PLA copolymer obtained by the preparation method of the present invention has higher tensile strength and greater elongation at break than the method of directly co-extruding PBST resin and PLA in the prior art. It can be seen that the preparation method of the present invention can obtain a high-strength, high-toughness PBST-PLA copolymer material, which greatly improves the use performance of the PBST-PLA copolymer material.

[0102] By comparing the test results of Example 1 and Comparative Example 3, it can be seen that the biodegradable PBST-PLA copolymer obtained in Example 1 has a greater tensile strength and a higher elongation at break, indicating that the preparation method of the present invention performs the esterification reaction separately, and the content of by-products in the product obtained in the esterification stage is lower, and thus the copolymer finally obtained has better mechanical properties.

[0103] From the test results of Comparative Example 1 and Comparative Example 4, it can be seen that the tensile strength and elongation at break of the copolymer product obtained by the method of adding PLA in the polymerization reaction stage are reduced compared with the preparation method of the present invention, indicating that the copolymer obtained by the preparation method of the present invention is superior to the method of adding PLA in the polymerization reaction stage.

[0104] Test Example 2

[0105] This test example investigates the effect of the copolymerization reaction time of PLA and PBST on the performance of the copolymer product obtained during the preparation process. Specifically, referring to the preparation method in Example 1, only the reaction time in step (4) was changed, and the other preparation steps and process parameters were the same as in Example 1, and the mechanical properties of the obtained PBST-PLA copolymer were tested, and the results are shown in Table 2 below.

[0106] Table 2 Mechanical properties test results

[0107] Reaction time / min Tensile strength / MPa Elongation at break / % 15 30 760 20 32 810 30 35 850 40 34 840 50 33 820

[0108] It can be seen from the above test results that by controlling the reaction time of the copolymerization stage to 20 to 50 minutes, a copolymer product with a tensile strength of not less than 32 MPa and an elongation at break of not less than 810% can be obtained. In the preferred embodiment of the present invention, by controlling the reaction time of the copolymerization stage to 30 to 40 minutes, a copolymer product with a tensile strength of not less than 34 MPa and an elongation at break of not less than 840% can be further obtained.

[0109] Test Example 3

[0110] This test example investigates the effect of the temperature of the copolymerization reaction of PLA and PBST on the performance of the resulting copolymer product during the preparation process. Specifically, referring to the preparation method in Example 1, only the reaction temperature inside the blending kettle in step (4) was changed, and the other preparation steps and process parameters were the same as in Example 1, and the mechanical properties of the resulting PBST-PLA copolymer were tested, and the results are shown in Table 3 below.

[0111] Table 3 Mechanical properties test results

[0112] Reaction temperature / ℃ Tensile strength / MPa Elongation at break / % 180 28 600 190 33 830 200 35 850 210 33 840 220 32 800

[0113] It can be seen from the above test results that when the reaction temperature in the copolymerization stage is lower than 190°C, for example, at 180°C, the tensile strength of the copolymer product is 28MPa, and the elongation at break is only 600%, both of which are at a relatively low level. If the reaction temperature in the copolymerization stage is controlled at 190-210°C, a copolymer product with a tensile strength of not less than 33MPa and an elongation at break of not less than 830% can be obtained. However, if the reaction temperature is further increased, the tensile strength and elongation at break of the obtained copolymer will decrease instead. Therefore, in the preparation method of the present invention, the reaction temperature of the copolymerization reaction is controlled at 190-210°C. Further preferably, the reaction temperature in the copolymerization stage is controlled at 200-210°C, and a copolymer product with an elongation at break of not less than 840% can be obtained, which has a better effect.

[0114] Test Example 4

[0115] This test example investigates the effect of the mass ratio of the first intermediate product to the second intermediate product on the performance of the copolymer product obtained during the preparation process. Specifically, referring to the preparation method in Example 1, only the mass ratio of the first intermediate product to the second intermediate product in step (3) was changed, and the other preparation steps and process parameters were the same as in Example 1, and the mechanical properties and biodegradability of the obtained PBST-PLA copolymer were tested, and the results are shown in Table 4 below.

[0116] In this test example, the biodegradation rate of the copolymer product was tested by the GB / T 19277 standard method, wherein the international degradation standard for biodegradable materials requires a biodegradation rate greater than 90%.

[0117] Table 4 Performance test results

[0118] Quality Ratio Tensile strength / MPa Elongation at break / % Biodegradation rate / % 1:0.8 34 900 98% 1:1.0 35 850 95% 1:1.2 36 600 90% 1:1.4 37 400 70% 1:1.6 37 380 60% 1:2.0 39 300 50% 1:2.5 39 260 46%

[0119] It can be seen from the above test results that as the mass proportion of the second intermediate product increases, the tensile strength of the obtained copolymer shows an upward trend, while the elongation at break and the biodegradation rate both show a downward trend. In the present invention, the mass ratio of the first intermediate product to the second intermediate product is controlled at 1:0.8-1.2, and a copolymer product with a tensile strength of not less than 34MPa, an elongation at break of not less than 600%, and a biodegradation rate of not less than 90% can be obtained. Further controlling the mass ratio to 1:0.8-1.0, a copolymer product with an elongation at break of not less than 850% and a biodegradation rate of not less than 95% can be obtained, ensuring that the obtained copolymer has both good mechanical properties and degradability.

[0120] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A method for preparing a biodegradable PBST-PLA copolymer, characterized in that: The following steps are involved: (1) mixing succinic acid, butanediol and a first catalyst to carry out an esterification reaction to obtain a first intermediate product; (2) mixing terephthalic acid, butanediol and a second catalyst to carry out an esterification reaction to obtain a second intermediate product; (3) mixing the first intermediate product, the second intermediate product and a polycondensation catalyst to perform a pre-polycondensation reaction to obtain a pre-polycondensation product; (4) The pre-polycondensation product is subjected to a final polycondensation reaction. After the polymerization reaches a certain molecular weight, the temperature is lowered, PLA is added to react, the product is discharged, and extruded and granulated to obtain a biodegradable PBST-PLA copolymer.

2. The method for preparing the biodegradable PBST-PLA copolymer according to claim 1, characterized in that: In step (4), the temperature is lowered to 190-210° C. and PLA is added to react, the reaction temperature is maintained at 190-210° C., and the reaction time is 20-50 min; Preferably, the reaction temperature is 200-210°C and the reaction time is 30-40 min; Preferably, after the reaction is completed, nitrogen is introduced to pressurize the material for discharging; Preferably, nitrogen is introduced and pressurized to 3-4 Kgf / cm 2 Carry out discharging.

3. The method for preparing the biodegradable PBST-PLA copolymer according to claim 2, characterized in that: In step (4), the reaction temperature of the final polycondensation reaction is 250-260° C., preferably 255-260° C.; Preferably, when the intrinsic viscosity of the melt is 1.25 to 1.30 dL / g, the temperature is lowered; More preferably, the final polycondensation reaction is carried out in a polymerization kettle, and when the intrinsic viscosity of the melt is 1.25-1.30 dL / g, the melt is transported to a blending kettle for cooling, and PLA is added.

4. The method for preparing the biodegradable PBST-PLA copolymer according to claim 3, characterized in that: During the final polycondensation reaction, the vacuum degree in the polymerization kettle is controlled to be 60 to 150 Pa, preferably 60 to 100 Pa; Preferably, the polymerization kettle is evacuated for a period of 40 to 70 minutes, preferably 50 to 60 minutes.

5. The method for preparing the biodegradable PBST-PLA copolymer according to any one of claims 1 to 4, characterized in that: In step (4), PLA is in powder form, the mesh size of PLA powder is 100-150 mesh, preferably 130-150 mesh, and the addition amount is 10%-25% of the mass of the melt, preferably 15%-20%; Preferably, in step (4), a functional additive is added after cooling, and the amount of the functional additive added is 0.05% to 0.10% of the mass of the melt; More preferably, the functional auxiliary agent is pyromellitic anhydride.

6. The method for preparing the biodegradable PBST-PLA copolymer according to any one of claims 1 to 5, characterized in that: In step (1), the molar ratio of succinic acid to butanediol is 1:1.20-1.30, preferably 1:1.25-1.30; in step (2), the molar ratio of terephthalic acid to butanediol is 1:2-4, preferably 1:2-3; Preferably, the first catalyst is tetrabutyl titanate, and the second catalyst is tetraisopropyl titanate; More preferably, the molar amount of the first catalyst is 0.01% to 0.03% of the molar amount of the succinic acid, preferably 0.02% to 0.03%; the molar amount of the second catalyst is 0.01% to 0.03% of the molar amount of the terephthalic acid, preferably 0.02% to 0.03%.

7. The method for preparing the biodegradable PBST-PLA copolymer according to any one of claims 1 to 6, characterized in that: In step (1), the reaction temperature of the esterification reaction is 165-175° C., preferably 165-170° C.; the esterification rate reaches 98%-99.5%, and the first intermediate product is obtained; In step (2), the reaction temperature of the esterification reaction is 245-255° C., preferably 250-255° C.; the esterification rate reaches 98%-99.5%, and the second intermediate product is obtained.

8. The method for preparing the biodegradable PBST-PLA copolymer according to any one of claims 1 to 7, characterized in that: In step (3), the mass ratio of the first intermediate product to the second intermediate product is 1:0.8-1.2, preferably 1:0.8-1.0; Preferably, the amount of the polycondensation catalyst is 0.02% to 0.04%, preferably 0.02% to 0.03%, of the total mass of succinic acid in step (1) and terephthalic acid in step (2); More preferably, the polycondensation catalyst is tetraisopropyl titanate.

9. The method for preparing the biodegradable PBST-PLA copolymer according to any one of claims 1 to 8, characterized in that: In step (3), the reaction temperature of the pre-polycondensation reaction is 230-245° C., and the reaction time is 30-50 min; Preferably, the reaction temperature of the pre-polycondensation reaction is 240-245° C., and the reaction time is 35-45 min.

10. A biodegradable PBST-PLA copolymer, characterized in that: The biodegradable PBST-PLA copolymer has a tensile strength of 35-40 MPa and an elongation at break of 600-900%. Preferably, the biodegradable PBST-PLA copolymer is prepared by the preparation method of the biodegradable PBST-PLA copolymer according to any one of claims 1-9.

Citation Information

Patent Citations

  • Biodegradable film blowing resin and preparation method of film

    CN114015210A